30 years of sublingual immunotherapy. Issue 5 (20th December 2019) - Passalacqua, Giovanni; Bagnasco, Diego; Canonica, Giorgio Walter
Abstract: Allergen Immunotherapy (AIT) was introduced in clinical practice on an empirical basis more than 100 years ago. Since the first attempts, AIT was administered subcutaneously. Indeed, other routes of administration were proposed and studied, in particular to improve the safety, but only the sublingual route (SLIT) achieved a credibility based on evidence and was then accepted as a viable "alternative" option to the subcutaneous route. SLIT was largely used in clinical trials and clinical practice in this last 30 years. Thus, a large amount of data is available, coming from either controlled trials and postmarketing surveillance studies. It is clear that SLIT is overall effective, but it is also clear that the efficacy is not "class‐related, " as derived from meta‐analyses, but restricted to each specific product. The 30‐year lasting use of SLIT allowed to clarify many clinical aspects, such as efficacy, safety, use in asthma, regimens of administration, and optimal doses. In parallel, the mechanisms of action of AIT were elucidated, and new indications were proposed (eg food allergy, atopic dermatitis). In addition, the introduction of molecular‐based diagnosis, allowed to better refine the prescription of SLIT, based on specific sensitization profiles. The present article will describe the origin and evolution of SLIT for respiratory allergy, taking into account the clinical context that suggested this form of treatment, the recently developed aspects, the future perspectives and unmet needs, This is not, therefore, a systematic review, rather a narrative historical description of the past history, and a look forward to the future opportunities.